The silver bullets of Annie Oakley - Lackey, Mercedes (Lackey, Mercedes. Elemental masters, 2022)
Annie Oakley has always suspected there is something "uncanny" about herself, but has never been able to put a name to it. But when Buffalo Bill's Wild West Show goes on tour through Germany, Bill temporarily hires a new sharpshooter to be part of his "World Wide Congress of Rough Riders." As they travel and perform, Annie must use her newfound knowledge and rare skill to combat creatures of the night scattered across the countryside, who threaten both the performers and the locals. Annie's got her gun, and it's filled with silver bullets.--